USE OF CANVA LEARNING MEDIA AS A MEANS OF SUPPORTING MATHEMATICS LEARNING AT SMK NEGERI 1 AMANDRAYA - Efron Manik; Buulolo, Derman; Halawa, Dedi Presli; Telaumbanua, Magdalena Susanti; Situmorang, Adi S (Universitas Nias Raya, 2023)
Learning in the all-digital 21st century era is required to be able to use and utilize existing technology so that the learning process is more interesting and creates learning that is able to increase students' thinking power as well as the creative power of students. This study aims to describe the use of the Canva application as a learning medium in mathematics. The Canva application is an online graphic design application in which several templates, images, various shapes and letters are provided. The Canva application is already available on smartphones so it can be used anywhere and anytime. As for this research is library research (library research). The research subject is the author as a key informant and the research object is in the form of articles related to the use of the Canva application in making learning media. By utilizing the Canva application, it makes it easier for teachers or educators to make math learning media more attractive to students.